The Routledge handbook of accounting ethics - Taylor, Eileen Z. (Routledge international handbooks, 2021)
"The perspective of this book is to present "ethics" as a conversation about how we decide what is good or bad, right or wrong. It is a collection of conversations employed by educators to assist accounting students in developing their understanding of accounting's ethical aspects and to help them develop into critical thinkers who consider the ethical complexities of the function of accounting in human society. As social beings, ethics is a central human concern, since it involves determining the ethicality of human actions and their effect on other individuals, as well as determining the collective societal acceptance or rejection of an action. Thus, the book's primary goal is to call attention to the intersectionality of accounting and ethics, and to encourage students and researchers to consider the ethical implications of accounting decisions. The book contains a diversity of perspectives within which discussions of accountant's and accountings' ethical responsibilities may occur. The contributing authors were deliberately chosen for their diverse perspectives on from whence moral guidance for accounting may come. Each chapter stands on its own and represents the thinking of its authors. The book is not a primer on correct behavior for accountants, but a place where educators may spur the conversation along"--